Senam Jantung Sehat untuk Kesehatan Masyarakat Desa Laguruda Kecamatan Sanrobone Kabupaten Takalar - Nurfitriani Nurfitriani; Nurul Hidayah Nur; Andi Niartiningsih (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Community service aims to provide an understanding of good living behavior to improve the health of people in an area. Through the implementation of socialization that has been carried out well, participants are given knowledge about how to maintain heart health so that personal, family, and entire village community awareness is formed to be able to implement it in their daily lives. Interactive and participatory socialization methods are used to invite participants to be active in learning. Before the socialization, participants filled out a questionnaire to measure their understanding and attitudes regarding maintaining heart health. The results of the questionnaire became the basis for an initial evaluation to determine the level of knowledge and awareness of participants before the socialization was carried out. After the socialization, participants were asked to fill out the same questionnaire to evaluate changes in their understanding, attitudes, and readiness for clean living. The evaluation results showed a significant increase in participants' understanding of how to maintain heart health. This evaluation indicates that heart health socialization has had a positive impact on participants in increasing their awareness and readiness for health. As a follow-up step, periodic monitoring and evaluation need to be carried out to ensure the sustainability of the understanding and attitudes that have been improved by participants. Collaboration with related parties such as the village or sub-district and the health office can also strengthen efforts to improve public health.